Institutionalization of disaster risk reduction and management program of De La Salle schools in Manila and Zobel-Muntinlupa - Lanada, Maria Isabel B. (Animo Repository, 2014)
Preparation for responding to emergency events that does not warrant outside help beyond the local school community resources or responding to disaster events that is beyond the capabilities of the schools requires professionalization and institutionalization of ORR Committee to function as a team for saving lives. To date, there is no emergency preparedness and disaster planning system that have been standardized at all levels across the various school policies. A preparedness program varies and entails a lot of work. This study intends to identify if Disaster Risk Reduction and Management (DRRM) principles is currently being adopted among Lasallian schools and to explore the perceptions and views of educators, students and administrators of De La Salle Schools in Manila and Muntinlupa (Zobel) in implementing emergency preparedness and disaster preparedness awareness programs into their school policies, if not already included. A quantitative data collection was employed in which one hundred seventeen (117) from the targeted 120 respondents completed an online survey questionnaire. Descriptive statistics was used to answer the research questions. Findings of this study indicated that majority of the respondents are aware in terms of preparedness and disaster training program of their schools, however, their perceived level of importance for inclusion of the emergency preparedness and massive information education campaign in school policies was high. The results of this study supported the need for establishing a set of standardized core emergency preparedness and disaster information campaign at De La Salle schools.